TRIPS FLEXIBILITIES AND INDIA’S PLANT VARIETY PROTECTION REGIME: THE WAY FORWARD - R. Moonka; S. Mukherjee (BRICS Law Journal, 2018)
Article 27.3(b) of the TRIPS Agreement provides that members shall provide for protection of plant varieties either by patents or by an effective sui generis protection or both. While WTO member countries can choose from among intellectual property strategies to protect plant varieties, they may not choose to exclude plant varieties from IP rights protection without facing trade sanctions from the WTO dispute resolution body. The open-ended language of the article creates a flexible standard of protection sympathetic to developing nations’ socio-economic priorities, provided that the effectiveness requirement is satisfied. This flexibility presents a range of possibilities from systems like the plant patent regime of the United States or specific variety protection systems of the European Union to the possibility of customized plant protection regimes suited to the needs of developing nations.India, while complying with the requirements of the TRIPS Agreement for the protection of plant varieties, enacted the Protection of Plant Varieties and Farmers’ Rights Act. The fundamental ideology of the PPVFR Act is to address India’s concerns about protecting the rights of small and marginal farming communities, while at the same time promoting plant breeding by vesting adequate IP rights protection which will boost further research and innovation in this field.This paper argues that as it is necessary to recognize and protect the rights of farmers in respect of their contribution made at any time in conserving, improving and making available plant genetic resources for the development of new plant varieties, the PPVFR Act has maintained a balance between breeders’ rights and farmers’ rights. The PPVFR Act protects farmers’ rights to save, use, exchange and share all farm produce, including seeds that fall within the purview of the Act, and it provides protection of indigenous knowledge against unwary monetization.